A qualitative study exploring counselling for release of information to participants of a donor-assisted conception programme. (June 2015) - Rodino, Iolanda S.; Chester, Helen; Harris, Maureen; Maslin-Prothero, Sian
Abstract Worldwide, donor-assisted conceptions are increasing with legislative reforms in some countries providing opportunities for participants of a donor-assisted conception programme, i.e. recipients, donors, donor-conceived adults and their genetically related siblings and half-siblings, to access information. Whilst policy and practice for accessing donor-identifying information vary, there has been no research exploring the perceptions and experiences of those who provide the service. This study aimed to explore the perceptions and experiences of Australian and New Zealand infertility counsellors who provide counselling for release of information to participants of a donor-assisted conception programme. Using a qualitative research design, in-depth interview data of six infertility counsellors were thematically analysed to identify key themes. We report the primary themes that emerged from the data which include professional perspectives on the role of counsellor in the counselling process, the professional and societal responsibility to provide counselling, and influences on professional practice. Findings from this qualitative study can be used as a platform for larger international studies on the clinical practice of donor information release and to inform clinical practice and service delivery. The implications of these results for policy and future longitudinal research are also discussed.